Celiac Disease and Autoimmune-Associated Conditions. (24th July 2013) - Lauret, Eugenia; Rodrigo, Luis
Abstract : Celiac disease (CD) is frequently accompanied by a variety of extradigestive manifestations, thus making it a systemic disease rather than a disease limited to the gastrointestinal tract. This is primarily explained by the fact that CD belongs to the group of autoimmune diseases. The only one with a known etiology is related to a permanent intolerance to gluten. Remarkable breakthroughs have been achieved in the last decades, due to a greater interest in the diagnosis of atypical and asymptomatic patients, which are more frequent in adults. The known presence of several associated diseases provides guidance in the search of oligosymptomatic cases as well as studies performed in relatives of patients with CD. The causes for the onset and manifestation of associated diseases are diverse; some share a similar genetic base, like type 1 diabetes mellitus (T1D); others share pathogenic mechanisms, and yet, others are of unknown nature. General practitioners and other specialists must remember that CD may debut with extraintestinal manifestations, and associated illnesses may appear both at the time of diagnosis and throughout the evolution of the disease. The implementation of a gluten-free diet (GFD) improves the overall clinical course and influences the evolution of the associated diseases. In some cases, such as iron deficiency anemia, the GFD contributes to its disappearance. In other disorders, like T1D, this allows a better control of the disease. In several other complications and/or associated diseases, an adequate adherence to a GFD may slow down their evolution, especially if implemented during an early stage.